MOLECULAR DATING OF INTRASPECIFIC DIFFERENTIATION OF THE STOAT (MUSTELA ERMINEA) BASED ON THE VARIABILITY OF THE MITOCHONDRIAL ND2 GENE - B. A. Malyarchuk; G. A. Denisova; M. V. Derenko (Вавиловский журнал генетики и селекции)
Nucleotide sequences of the NADH dehydrogenase subunit 2 gene (ND2) of mitochondrial DNA (mtDNA) were determined in stoats (Mustela erminea) from northeastern Kamchatka. Analysis of the data on ND2 variability in stoats presented here and in earlier studies shows that the divergence level between American and Eurasian mtDNA haplotypes is about 5 %, whereas that among Eurasian ones is as low as 0,5 %. The results of phylogenetic analysis also point to a highly significant differentiation between the American and Eurasian mtDNA lineages, whereas a single Kamchatkan cluster of mtDNA haplotypes is recognized in the Eurasian mtDNA clade with high confidence. Molecular dating shows that the separation of ancestral population of the stoat occurred approximately 1,3–1,6 million years before present (BP), but the Eurasian mtDNA lineages diverged about 300 thousand years (ka) BP. The evolutionary age of Kamchatkan mtDNA haplotypes is about 95–120 ka, which contradicts the suggestions of other authors about post-last glacial (19–26,5 ka BP) recolonization of Eurasia by stoat populations. This inconsistency is discussed.